Opening doors the early Netherlandish triptych reinterpreted - Jacobs, Lynn F. 1955- (Pennsylvania State Univ. Press, 2012)
"A study of Netherlandish triptychs from the early fifteenth century through the early seventeenth century, covering works by Jan van Eyck, Rogier van der Weyden, Hugo van der Goes, Hieronymus Bosch, and Peter Paul Rubens. Explores how the triptych format structures and generates meaning" - Provided by publisher